Brill's companion to Seneca, philosopher and dramatist - Damschen, Gregor.; Heil, Andreas, 1969- (Brill's Companions to Classical Studies., 2014)
This new and important introduction to Seneca provides a systematic and concise presentation of this author's philosophical works and his tragedies. It provides handbook style surveys of each genuine or attributed work, giving dates and brief descriptions, and taking into account the most important philosophical and philological issues. In addition, they provide accounts of the major steps in the history of their later influence. The cultural background of the texts and the most important problem areas within the philosophic and tragic corpus of Seneca are dealt with in separate essays.